Analysıs Of The Mıxed Realıty Adoptıon Process Usıng The Dıffusıon Of Innovatıon Theory In The Creatıve Industry In Indonesıa - Dodie Tricahyono; Indra Laksana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Technology is rapidly evolving and inevitably affecting humanity. Individuals living in the smartphone era are directly or indirectly compelled to adapt to advancements in information and communication technology. One such technology is the Metaverse, a virtual world where people can interact with each other within a three-dimensional software environment known as Mixed Reality. In Mixed Reality, various activities can be performed and utilized by different groups, particularly businesses in the creative industry. However, the effective use of Mixed Reality requires appropriate processes by prospective users. When an innovation is communicated through various channels over a specific period within a social system, it is referred to as the Diffusion of Innovations theory. In Indonesia, Mixed Reality innovation is not yet widely recognized by the public, and only a few entrepreneurs fully understand and are familiar with Mixed Reality. The Diffusion of Innovations theory outlines five stages in the adoption of an innovation, where individuals face two options: adoption or rejection. In this study, the author will use a qualitative method by observing variables related to technology adoption. This research will process data by conducting interviews with a community that has previously used technology, either directly related to Mixed Reality.